PERSUASIVE LINGUISTIC STRATEGIES IN DIGITAL TOURISM: DISCOURSE ANALYSIS OF THE DOLAN BANYUMAS WEBSITE - Gigih Ariastuti Purwandari; Indah Puspitasari; Kristianto Setiawan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study analyses persuasive linguistic strategies on the Dolan Banyumas tourism website to examine how promotional discourse constructs destination image and shapes audience perception. Using qualitative discourse analysis, the study examines promotional texts across key sections of websites, including homepage narratives, destination descriptions, cultural content, and calls-to-action. The findings reveal that persuasive discourse is effective through the integration of emotional engagement, experiential storytelling, and credibility-oriented information, presenting Banyumas as an attractive, accessible, and culturally distinctive destination. The website strategically combines evocative language with informative content to enhance affective appeal while maintaining institutional legitimacy. A key contribution of this study is its identification of vernacular affective language, particularly the local expressions ngangeni and mbetaih, which function as symbolic resources to reinforce authenticity and emotional attachment in digital tourism promotion. The study contributes theoretically and methodologically to tourism discourse and digital discourse analysis by demonstrating how persuasive language functions across promotional contexts. Practically, the findings offer insights for culturally sensitive digital place branding, highlighting the value of local affective expressions in strengthening destination image and audience engagement.